Planning and Policy: Synergy to Effective Open and Distance Learning Administration in Nigeria - Oladejo, Maruff Akinwale (ATIKAN, 2014)
ABSTRACT: Considering the consequential roles Open and Distance Learning (ODL) is currently playing in ensuring educational delivery at doorsteps of those who desire it, it becomes highly imperative that its administration needs to be effective so that the goals for which it was introduced are achieved. This paper considers planning and policy as synergy to effective Open and Distance Learning administration in Nigeria. Four modes of operation in ODL, namely single, dual, mixed, and consortia, were equally highlighted. The author also discussed some of the critical areas like communication system, learnersâ support, staff personnel appraisal, as well as nature and quantity of resources that require effective planning. Furthermore, some policy implications which bother on issues such as quality assurance, the use of technology, inclusiveness, and staff supports were brought to the fore. It was concluded that ODL has truly become an accepted and essential part of the main-stream of educational systems in both developed and developing countries. Finally, the paper recommends inter alia the need for ODL curriculum designers to ensure flexibility so as to accommodate the needs and experiences of a range of diverse people, provision of effective supports for the learners and the participating staff, the ODL environment to be more accommodating, stimulating, and motivating for the distance learners.KEY WORD: Administration, open and distance learning, planning, policy, synergy effective, communication system, and staff and learnersâ supports.IKHTISAR: âPerencanaan dan Kebijakan: Sinergi untuk Mengefektifkan Pengurusan Belajar Jarak Jauh dan Terbuka di Nigeriaâ. Mengingat peran yang konsekwen dari Belajar Jarak Jauh dan Terbuka (BJJT) saat ini adalah untuk memastikan ketersediaan pendidikan dari rumah ke rumah bagi orang-orang yang menginginkannya, menjadi sangat penting bahwa pengurusannya harus efektif sehingga tujuan yang diperkenalkan tercapai. Makalah ini menimbang perencanaan dan kebijakan yang sinergis untuk mengefektifkan pengurusan Belajar Jarak Jauh dan Terbuka di Nigeria. Empat gaya pelaksanaan dalam BJJT, yaitu tunggal, ganda, campuran, dan konsorsium, sama-sama akan dikaji. Penulis juga membahas beberapa bidang penting seperti sistem komunikasi, dukungan peserta didik, staf tenaga penilaian, serta sifat dan kuantitas sumber daya yang membutuhkan perencanaan yang efektif. Selain itu, beberapa implikasi kebijakan yang mengganggu pada isu-isu seperti jaminan kualitas, penggunaan teknologi, sikap inklusif, dan dukungan staf, juga didahulukan. Disimpulkan bahwa BJJT telah benar-benar menjadi bagian yang diterima dan penting dalam arus utama sistem pendidikan, baik di negara maju maupun berkembang. Akhirnya, makalah ini merekomendasikan antara lain kebutuhan bagi para perancang kurikulum BJJT untuk memastikan fleksibilitas sehingga dapat mengakomodasi berbagai kebutuhan dan pengalaman yang beragam, penyediaan dukungan yang efektif bagi peserta didik dan partisipasi staf, lingkungan BJJT yang lebih akomodatif, merangsang, dan memotivasi peserta didik belajar jarak jauh.KATA KUNCI: Pengurusan, belajar jarak jauh dan terbuka, perencanaan, kebijakan, sinergi yang efektif, sistem komunikasi, serta dukungan staf dan peserta didik.About the Author: Maruff Akinwale Oladejo, Ph.D. is a Lecturer at the Faculty of Education, University of Lagos, Akoka, Nigeria. For academic interests, the author is able to be contacted via phone at: +2348128284836 and e-mail at: maoladejo@unilag.edu.ngHow to cite this article? Oladejo, Maruff Akinwale. (2014). âPlanning and Policy: Synergy to Effective Open and Distance Learning Administration in Nigeriaâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.4(2) December, pp.275-282. Bandung, Indonesia: Minda Masagi Press, FKIP UNSUR Cianjur, and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (July 2, 2014); Revised (August 7, 2014); and Published (December 27, 2014).